1980
DOI: 10.1128/aac.18.5.746
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Metabolism of Potassium Phosphanilate in Laboratory Animals and Humans

Abstract: Phosphanilic acid is an antibacterial agent with a mode of action and antibacterial spectrum similar to those of sulfamethoxazole, with the exception that it has potent antipseudomonal activity. Bioavailability studies in rats (50, 300, and 600 mg/kg, oral and subcutaneous), dogs (50, 150, and 450 mg/kg, oral and intravenous infusion), and humans (400 and 800 mg, oral) showed that the extent of oral absorption of potassium phosphanilate was low. The bioavailability, calculated by comparing the oral values for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…administration were substantially lower than those of S. N-acetylated P was not detected in the urine of mice by the assay method used. However, it has been reported that P (8,13), like the sulfonamides (12,15), is metabolized in rats and humans to the antimicrobially inactive N-acetylated derivative which is rapidly excreted in the urine. When given p.o.…”
mentioning
confidence: 99%
“…administration were substantially lower than those of S. N-acetylated P was not detected in the urine of mice by the assay method used. However, it has been reported that P (8,13), like the sulfonamides (12,15), is metabolized in rats and humans to the antimicrobially inactive N-acetylated derivative which is rapidly excreted in the urine. When given p.o.…”
mentioning
confidence: 99%